(untitled) - Huston, Perdita (New York, 1992)
To honor the 40th anniversary of the International Planned Parenthood Federation, journalist Perdita Huston travelled the world to gather this remarkable collection of oral histories of and about the often unknown leaders of a worldwide movement to bring women their reproductive rights. Drawing on personal interviews, Huston delineates the motivations, strategies, and heartaches of twelve pioneers-eight women, four men-both from the developing world, before and after colonial rule, and from industrialized countries, who braved scorn and abuse to raise the issues of family planning, contraception, and sex education, and to fight for improved healthcare for women.
Keywords: Birth control,Birth control; Biography,Cross-cultural studies